Jamaica : Second Review Under the Stand-By Arrangement and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Jamaica. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Jamaica's Second Review under the Stand-by Arrangement and Request for Modification of Performance Criteria (PCs). Jamaica's economy is showing sustained signs of activity, but growth remains vulnerable to the weather. Inflation and the current account deficit are low, helped by relatively stable oil prices and the government's policy efforts. The historically low yields in the recent global bond reopening reflect Jamaica's hard-won credibility. Program implementation remains strong. All PCs and structural benchmarks for the end of June were met. The landmark public pension reform bill was passed by Parliament. Based on continued strong program implementation and reform commitments, the IMF staff recommends completion of the second review.